Handling staff and communications at Portland Aluminium - Russell, Geoff (Bendigo, Vic. : Video Education Australasia, 1992)
This program looks at the specific roles of human resource manages in recruitment, induction, training, appraisal and motivation. It also stresses the importance of good corporate communication in providing human resources services
Title from title screen
Executive producer, Neil Barrett
Narrator: Geoff Russell
DVD format
Keywords: Portland Aluminium (Vic.); Personnel management; Communication in personnel management